Mesolithic Fireplaces and the Enculturation of Early Holocene Landscapes in Britain, with a Case Study from Western Scotland. (15th December 2019) - Mithen, Steven
Abstract : In light of the enculturation of landscapes by ethnographically documented hunter-gatherers, we should expect Mesolithic hunter-gatherers to have endowed their early Holocene landscapes with meaning. Attempts to find evidence for this have focussed on the unusual and exotic – those aspects of the archaeological record that seem immediately unrelated to subsistence. In this contribution, I suggest that fireplaces, ubiquitous on Mesolithic sites and often swiftly passed over in site reports as evidence for cooking alone, had played a key role in the process of landscape enculturation. Although we cannot reconstruct the specific meanings once attached to early Holocene landscapes, by appreciating the social and cultural significance of fireplaces we gain a more holistic view of the Mesolithic than is currently the case, whether in those studies that focus on settlement and subsistence or those that cite examples of ritual. In the course of making this argument, I summarise the evidence for fireplaces from Mesolithic Britain, noting the need for more systematic reporting. Finally, I provide a case study from western Scotland that seeks to view a suite of fireplaces in the context of the landscape topography, early Holocene environments, subsistence economy, and by drawing on selected ethnographic analogies.